The Degree to Which 6 Grade Students Possess Language Skills Considering Blended Learning from the Point of View of their Teachers in Jordan - Ta'amneh, Ahmed Ali Mahmoud; Al-Fayoumi, Khalil (Journal of Curriculum and Teaching Methodology, 2022)
The current study aimed to identify the degree to which sixth grade students possess language skills in Arabic language considering blended learning from the point of view of their teachers in Jordan. To achieve the objectives of the study, the descriptive survey method was adopted, and the study tool consisted of developing a questionnaire consisting of (41) items divided into four skills, the validity and reliability of which were verified according to the methodological foundations, and it was applied to a sample of (45) male and female teachers of the sixth grade In the Northern Jordan Valley and Koura District in Irbid Governorate, it was chosen by random available method, and the results showed that the degree to which sixth grade students possess conversational, reding skills and writing skills under blended education from the teachers’ point of view came to a medium degree, and the results showed that the degree to which sixth grade students possess listening skills under blended education from the point of view of their teachers came to a large degree, The results showed that there were no statistically significant differences in the responses of the sample members about the degree to which sixth-grade students possess language skills under blended education, according to the variables, gender, educational qualification, expertise. The study recommended several recommendations, including holding training courses for Arabic language teachers on the use of technology and communication skills in blended education, and the use of various computer applications in developing reading, writing, speaking, and listening skills in the primary school classes and over long periods of time.
Keywords: language skills; blended learning; grade six basic; the level of gaining skills